Brettanomyces bruxellensis phenotypic diversity, tolerance to wine stress and wine spoilage ability. (May 2020) - Cibrario, Alice; Miot-Sertier, Cécile; Paulin, Margot; Bullier, Bastien; Riquier, Laurent; Perello, Marie-Claire; de Revel, Gilles; Albertin, Warren; Masneuf-Pomarède, Isabelle; Ballestra, Patricia; Dols-Lafargue, Marguerite
Abstract: Brettanomyces bruxellensis is a yeast species found in many fermented matrices. A high level of genetic diversity prevails in this species and was recently connected with tolerance to sulfur dioxide, the main preservative used in wine. We therefore examine other phenotypes that may modulate the ability of the species to spoil wine, in a selection of representative strains. The species shows a fairly high homogeneity with respect to the carbohydrates that can support growth, but more diverse behaviors regarding tolerance to low pH or ethanol. Thought no clear link can be drawn with genotype, some strains appear more tolerant than the others, mainly in the AWRI1499 like genetic group. Volatile phenol production is ubiquitous within the species, independent from yeast growth profile and not affected by the nature of the growth substrate. The specific production. n rate of volatile phenol production raises in case of increased aeration. It is little affected by pH decrease until 3.0 or by ethanol concentration increase up to 12% vol, but it decreased in case of increased constraint (pH < 3.0, Ethanol ≥14% vol) or combination of constraints. All the strain studied have thus the ability to spoil wine but some outstanding dangerous strains can even spoil the wine with high level of constrainst. Highlights: Most of the B. bruxellensis strains examined metabolize the same carbohydrates. All produce volatile phenols, whatever their growth profile or genetic group. A few AWRI1499 like strains are highly tolerant to ethanol and low pH. Only extreme pH and ethanol concentration alter phenol production. The most tolerant strains may even spoil the wines with high level of constraint.